Whoever Stole My Bike Is Gonna Get It - Mara, Will (New York : West 44 Books, 2022)
No one messes with Izzy Jeen and gets away with it. But then one day, Izzy finds that her beloved bike has been stolen! Who would do such a thing? Izzy insists that everyone help her launch a full-blown investigation at once. She vows to find the culprit and make them sorry that they ever stole from Izzy Jeen "the Big Mouth Queen" Marino.
Keywords: English fiction; Bicycles -- Juvenile fiction; Theft -- Juvenile fiction; Stealing -- Juvenile fiction